Acid-labile polyrotaxane exerting endolysosomal pH-sensitive supramolecular dissociation for therapeutic applications. Issue 21 (7th June 2015) - Nishida, Kei; Tamura, Atsushi; Yui, Nobuhiko
<x xml:space="preserve">Abstract</x> For achieving pH-sensitive dissociation and the subsequent release of threaded cyclic molecules from polyrotaxanes (PRXs) in weakly acidic environments, a novel acid-labile Pluronic/β-cyclodextrin-based PRX bearing ketal linkages was designed and its potential biomedical application was demonstrated.